2013
DOI: 10.1186/1471-2458-13-708
|View full text |Cite
|
Sign up to set email alerts
|

The burden of pediatric diarrhea: a cross-sectional study of incurred costs and perceptions of cost among Bolivian families

Abstract: BackgroundWorldwide, acute gastroenteritis represents an enormous public health threat to children under five years of age, causing one billion episodes and 1.9 to 3.2 million deaths per year. In Bolivia, which has one of the lower GDPs in South America, an estimated 15% of under-five deaths are caused by diarrhea. Bolivian caregiver expenses related to diarrhea are believed to be minimal, as citizens benefit from universal health insurance for children under five. The goals of this report were to describe tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
7
28
0
5
Order By: Relevance
“…These findings concur with those from a study in Bolivia which indicated that indirect costs still impeded access to paediatric care irrespective of user fee abolition. 14 One of the main contributors to total household costs was the value of time lost in the process of seeking care. This contributor was however measured subjectively from the verbal reports of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…These findings concur with those from a study in Bolivia which indicated that indirect costs still impeded access to paediatric care irrespective of user fee abolition. 14 One of the main contributors to total household costs was the value of time lost in the process of seeking care. This contributor was however measured subjectively from the verbal reports of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo, las gastroenteritis agudas presentan una carga económica tanto para los sistemas de salud como para la familia del paciente. Diversos estudios han caracterizado los costos directos e indirectos vinculados con los episodios de diarrea (MacIntyre & de Villiers, 2010;Alsan et al, 2011;Burke et al, 2013). Los costos médicos directos comprenden la consulta, las pruebas diagnósticas (estudios de sangre, orina y materia fecal), el tratamiento (sales de rehidratación oral, soluciones de dextrosa, solución fisiológica, suplementos vitamínicos, antibióticos) y cualquier otro gasto realizado previamente.…”
Section: Generalidades E Impacto Socioeconómicounclassified
“…Los costos médicos directos comprenden la consulta, las pruebas diagnósticas (estudios de sangre, orina y materia fecal), el tratamiento (sales de rehidratación oral, soluciones de dextrosa, solución fisiológica, suplementos vitamínicos, antibióticos) y cualquier otro gasto realizado previamente. Estos costos pueden oscilar entre el 1-5% del ingreso anual familiar, situación que puede llegar a empeorar en el caso de aquellas familias que no poseen un empleo formal o bien residen en áreas rurales o periurbanas, donde los ingresos suelen ser menores (MacIntyre & de Villiers, 2010;Burke et al, 2013). Dentro de los costos no médicos, se incluyen los gastos en comida durante la hospitalización del niño o durante la espera en el consultorio pediátrico, el transporte del hogar al centro asistencial y los cuidados relacionados a la estadía del niño en la internación (incluyendo pañales y comida).…”
Section: Generalidades E Impacto Socioeconómicounclassified
See 2 more Smart Citations